Assessing the impact of human activities on the health condition of the Lukosi River catchment using selected physico-chemical parameters as indicators of water quality - Nyagongo, Ahmad A.; Ndibalema, Vedasto G.; Lalika, Makarius C. S. (Frontiers in Water, 2024)
The Lukosi River catchment plays a crucial role in the economic and ecological framework of the country, serving as a major contributor to the Great Ruaha River (GRR). This study aimed to assess the impact of human activities on the health of the Lukosi River by analyzing key water parameters. Three sampling sites across the catchment were selected, and water samples were collected and analyzed using the American Public Health Association technique. A one-sample t-test was used to measure the significance of the difference between the measured water quality parameters and the water quality criteria established by the Tanzania Bureau of Standards (TBS) and the World Health Organization (WHO). The results revealed mean values for various parameters: pH (8.67 ± 0.57), temperature (24.803 ± 1.361°C), EC (93.30 ± 3.34 mgL−1), BOD (14.85 ± 1.49 mgL−1), TDS (46.95 ± 1.55 mgL−1), total hardness (27.53 ± 1.28 mgL−1), DO (3.4 ± 0.53 mgL−1), turbidity (109.83 ± 40.99 mgL−1), NO2 (79.04 ± 0.73 mgL−1), Cu (6.07 ± 0.60 mgL−1), Ca (7.88 ± 0.36 mgL−1), Mn (0.16 ± 0.07 mgL−1), Cl (7.58 ± 3.97 mgL−1), F (0.12 ± 0.0008 mgL−1), SO4 (20.42 ± 4.12 mgL−1), Mg (1.92 ± 0.13 mgL−1), Zn (0.14 ± 0.11 mgL−1), Fe (3.56 ± 0.15 mgL−1), and NH3 (4.67 ± 0.51 mgL−1). Parameters such as DO, turbidity, NH3, NO3, and BOD significantly (p = 0.05) exceeded the permissible limits set by the TBS and the WHO. Furthermore, elements including Fe and Cu exceeded allowable limits. Moreover, the WQI was used to indicate that the water in the catchment is unsuitable for sustaining aquatic organisms and is unfit for domestic use. Household questionnaires and direct observations identified key human activities in the catchment: gardening (78.3%), agriculture (68%), livestock keeping (50%), sand mining (21%), and brick-making (21%). Less prevalent were car washing (7%) and fishing (4%). These findings underscore the urgent need for conservation efforts and sustainable management practices to safeguard the Lukosi River catchment (LRC).